Barriers to entry, deregulation and workplace training: A theoretical model with evidence from Europe - Andrea Bassanini; Giorgio Brunello (Center for Economic Studies and ifo Institute (CESifo), 2010)
We study the impact of barriers to entry on workplace training. Our theoretical model indicates that there are two contrasting effects of deregulation on training. With a given number of firms, deregulation reduces the size of rents per unit of output that firms can reap by training their employees. Yet, the number of firms increases, thereby raising output and profit gains from training and improving investment incentives. The latter effect always prevails. Our empirical analysis, based on repeated cross-section data from 15 European countries and 12 industries, confirms the predictions of the model and shows that deregulation increases training incidence.
Keywords: J24; L11; O43; 330; training; product market competition; Europe; Deregulierung; Markteintritt; Betriebliche Bildungsarbeit; Bildungsinvestition; Theorie; EU-Staaten